Apakah bumdes sudah taat pada good governance? - Nindya Krismonica Titania; Intiyas Utami (Universitas Negeri Malang, 2021)
AbstractThe aim of this study is to observe the practice of BUMDes’ governance in the perspective of good governance government. In theoretical framework, BUMDes should be managed by concept of good governance government. However, the core problem relates to whether the BUMDes has been properly managed with the concept of good governance government or not. This study used interpretive paradigm with case study method. The research data was collected from informant involved in the management and activities of BUMDes. The result of this study shows that a rural fund has been considered as an BUMDes’ initial capital. Additionally, this research also reveals that: people attendance in a rural meeting has been considered as a form of participation; rural website and whatapp group have reflected transparency; ineffective accounting practice has represented a poor financial accountability.AbstrakPenelitian ini bertujuan untuk memahami tatakeloa Badan Usaha Milik Desa (BUMDes). Secara teoritis BUMDes sehasusnya dikelola dengan konsep good governance government. Namun, fokus permasalahan terletak pada pengelolaan BUMdes yang sesuai atau tidak sesuai dengan konsep tersebut. Penelitian ini menggunakan paradigma intepretif dengan metode studi kasus. Data penelitian bersumber dari informan yang terlibat dan terkait dalam pengelolaan dan kegiatan BUMDes. Temuan penelitian ini antara lain dana desa sebagai modal awal BUMDes, kehadiran masyarakat dalam musyawarah desa dimaknai sebagai bentuk partisipasi, keberadaan website desa dan grup whatsapp sebagai bentuk ransparansi, dan belum berjalannya praktik akuntansi sebagai bentuk akuntabilitas keuangan.